Advanced Gear Design Of Sms Group - Marcus Vinicius Laudares Mendonça (Associacao Brasileira de Metalurgia, Materiais e Mineracao, 2017)
SMS calculates and improves tooth and flank profiles individually to realise a homogeneous pressure distribution over the complete load flank. With a tooth profile and flank profile according to AGMA, ISO or DIN standard the contact pressure varies along the load flank. To realize a homogeneous distribution of the contact pressure and to avoid a premature mesh, SMS improves the tooth profile and flank profile in three steps. First SMS is doing a preliminary calculation and design according ISO, DIN or AGMA standard, with safety factors based on more than 125 years of experience. Second SMS calculates and checks the local contact pressure at the load flank under consideration of shaft, gearing and housing deformation, as well as the bearing behaviour. Finally SMS calculates and designs an improved tooth profile and flank profile to receive a homogeneous contact pressure at the load flank. The result is an increase of the torque transmitting capacity of up to 30% of the SMS advanced gears with the same outer dimensions than traditional gears.